The Effectiveness of Public Service Centers in Medan City, North Sumatra Province - Nindya Adhisty (Sean Institute, 2025)
This study examines the effectiveness of the Public Service Mall (MPP) in Medan City, North Sumatra Province, focusing on its ability to provide efficient and accessible public services. This study employed qualitative methods with data collection techniques including direct observation, interviews, and document analysis. The data analysis technique employed was thematic analysis. This method was used to evaluate the extent to which the MPP has achieved its objectives and identify factors that hinder its effectiveness, as well as to explore strategies to improve the efficiency of services provided at the Medan City MPP. The results of this study indicate that the implementation of the Medan City MPP has, in principle, demonstrated a concept for achieving its objectives, particularly in the aspect of providing public services under one roof that facilitates public access to various services. However, overall effectiveness remains low. This is indicated by the gap between the formulated objectives and actual results in the field. Several indicators, such as service speed, procedural consistency, and integration between agencies, still require significant improvement.